Nilai Komunikasi Profetik dalam Isi Regulasi Penyiaran Indonesia - Cepian (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2018)
Following the 1998 Reform, the Indonesian Broadcasting Commission (KPI) was established as an auxiliary state institution under Law No. 32 of 2002. This study explores the prophetic values within KPI regulations using qualitative methods and content analysis. The findings reveal four key values: divinity, national integrity and unity, humanization, and liberation. Recommendations include further examination of regulations by da'wah experts, increased dissemination of broadcasting rules, and regulatory revisions to strengthen prophetic values in Indonesia’s broadcasting system.